The physical sequelae of perinatally acquired HIV in adolescents - Comley-White, Nicolette (My University, 2022)
Human immunodeficiency virus (HIV) is a global challenge and with the continuously improving access to antiretroviral therapy (ART) the disease profile has shifted requiring chronic management. This holds true across the lifespan, and the generation of children with perinatal HIV who were born at the advent of early ART access have now aged into adolescence and young adulthood. Many perinatally HIV-infected adolescents (PHIVA) started ART at a young age and have spent their lifetime living with both the virus and on ART, two factors which have known neurotoxic effects. While the literature shows a clearly negative impact of perinatal HIV on adolescent neurocognitive development, there is limited information available on the physical sequelae that PHIVA may have. Thus, over three phases, the aim of this study was to determine the perceived physical challenges for PHIVA, to investigate the challenges clinically, and to propose a model of care for PHIVA. Human immunodeficiency virus (HIV) is a global challenge and with the continuously improving access to antiretroviral therapy (ART) the disease profile has shifted requiring chronic management. This holds true across the lifespan, and the generation of children with perinatal HIV who were born at the advent of early ART access have now aged into adolescence and young adulthood. Many perinatally HIV-infected adolescents (PHIVA) started ART at a young age and have spent their lifetime living with both the virus and on ART, two factors which have known neurotoxic effects. While the literature shows a clearly negative impact of perinatal HIV on adolescent neurocognitive development, there is limited information available on the physical sequelae that PHIVA may have. Thus, over three phases, the aim of this study was to determine the perceived physical challenges for PHIVA, to investigate the challenges clinically, and to propose a model of care for PHIVA. The first phase of the study was a qualitative analysis of the perceived physical challenges that PHIVA encounter. Participants were sourced from an HIV research and services clinic in Johannesburg, South Africa (for all phases of data collection) and 19 individuals were interviewed. All of the participants had early ART initiation (1 year 9 months; SD±1 year 2.3 months) and were virally suppressed, and only one adolescent reportedly did not experience any physical difficulties. The emerging codes were classified into categories of physical challenges, psychosocial challenges and other health issues. The results showed that PHIVA often experience challenges such as decreased endurance, pain and fatigue. They also struggle with decreased community participation, reduced muscle strength and motor skill, and emotional and cognitive impairments. The second phase of the study was a quantitative, cross-sectional analysis of 147 PHIVA and 102 HIV-negative adolescents as a comparison group. The participants were assessed across a range of physical functioning outcome measures for height, weight, fatigue, motor performance (with manual dexterity, balance, and aiming and catching subscales), peripheral neuropathy, muscle strength, endurance and disability. The results found that the PHIVA group had significantly more impairments than the comparison group for height (p<0.001), weight (p<0.001), body mass index (p=0.004), fatigue intensity (p=0.022), manual dexterity (p=0.021), balance (p=0.020) and disability levels (p=0.023), specifically within mobility (p=0.014), self-care (p=0.047) and participation (p<0.001). As with the adolescents of the first phase of data collection, these participants had initiated ART at an early age (8.5 months; SD±6.6 months) and 87% of the group were virally suppressed. Despite being well managed it is clear that PHIVA experience significant physical sequelae. The results of the study were used to develop a model of care for PHIVA. The model was validated through focus groups with PHIVA and healthcare providers who work in the field of HIV and adolescence. Input was given on the importance of different physical components as sequelae of perinatal HIV, and the roles of the healthcare providers were discussed. After the focus groups the model of care was finalised and a simplified schematic was designed. The results of the study were used to develop a model of care for PHIVA. The model was validated through focus groups with PHIVA and healthcare providers who work in the field of HIV and adolescence. Input was given on the importance of different physical components as sequelae of perinatal HIV, and the roles of the healthcare providers were discussed. After the focus groups the model of care was finalised and a simplified schematic was designed.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022